Pembelajaran Ilmu Pengetahuan Sosial pada Era Globalisasi - Silaban, Florensia; Manurung, Mario; Simanjuntak, Rian; Yunita, Sri (Indo-MathEdu Intellectuals Journal, 2024)
The development of technology, communication, and information continues to increase in line with the inevitable flow of globalization. Globalization has a great impact on various aspects, especially education, where educators are required to be creative, master a wide range of skills and knowledge. This study uses a qualitative method with literature studies to examine various relevant literature in answering social studies learning problems in the era of globalization and cultural diversity. The main source of data is articles published in various scientific journals and indexed in the database on Google Scholar. The research stages consist of collecting literature, reading carefully, coding data, classifying data, and drawing conclusions. The results of the analysis show that in education, globalization has a great impact with technological advances that support this field, demanding that educators master diverse knowledge and skills. Although social studies are often underestimated, globalization brings positive and negative influences. The positive is the acceleration of the development of science, technology, and information, while the negative is the emergence of consumptive behavior. Social studies learning plays a role in developing people's social skills in the midst of globalization, equipping students with knowledge related to global issues around them